Transformasi Tata Kelola Lembaga Ekonomi Pedesaan: Studi Kasus Dinamika Kelembagaan di Desa Bioa Sengok: (Transformation of Rural Economic Institution Governance: A Case Study of Institutional Dynamics in Bioa Sengok Village) - Abdul Aziz Zulhakim (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
The transformation of rural economic institutions in Indonesia is becoming more complex. This is due to the emergence of the Merah Putih Village Cooperative policy, which now intersects with existing Village-Owned Enterprises (BUM Desa, autonomous business entities established by villages to manage local assets and improve community welfare). This study addresses a key question: How does the governance of rural economic institutions transform in the context of institutional dynamics between sub-optimal BUM Desa and the Merah Putih Village Cooperative programme (a government-initiated cooperative aiming to unify and strengthen village economies)? The research uses a qualitative approach and a case study in Bioa Sengok Village, Lebong District. Data was collected through focus group discussions with village officials, local business actors, professional assistants, and local government. The data was then analysed through gradual coding: open, axial, and selective. The findings reveal the transformation occurred in four phases—initiation, local response, adaptation, and partial implementation. Each phase reflects negotiations between top-down policies and local adaptive capacities. Strong social capital, based on trust and communal norms, was a key supporting factor. In contrast, regulatory uncertainty, technical limits of the administrative system, conflicts of authority, and a lack of cross-sectoral coordination were significant structural obstacles. This study introduces dual institutional transformation (the simultaneous evolution of two interacting economic institutions within a village ecosystem) to describe the dynamic interaction between these entities. The practical implications emphasise the need for institutional synchronisation, gradual participatory transformation, multidimensional capacity building, and appreciation of the local institutional ecosystem. These steps will help ensure the rural economy remains sustainable and rooted in its local socio-economic context.